A bi-modal function of Wnt signalling directs an FGF activity gradient to spatially regulate neuronal differentiation in the midbrain - Dyer, Carlene; Blanc, Eric; Hanisch, Anja; Roehl, Henry; Otto, Georg W; Yu, Tian; Basson, M A; Knight, Robert (Development (Cambridge), 2014)
FGFs and Wnts are important morphogens during midbrain development, but their importance and potential interactions during neurogenesis are poorly understood. We have employed a combination of genetic and pharmacological manipulations in zebrafish to show that during neurogenesis FGF activity occurs as a gradient along the anterior-posterior axis of the dorsal midbrain and directs spatially dynamic expression of the Hairy gene her5. As FGF activity diminishes during development, Her5 is lost and differentiation of neuronal progenitors occurs in an anterior-posterior manner. We generated mathematical models to explain how Wnt and FGFs direct the spatial differentiation of neurons in the midbrain through Wnt regulation of FGF signalling. These models suggested that a negative-feedback loop controlled by Wnt is crucial for regulating FGF activity. We tested Sprouty genes as mediators of this regulatory loop using conditional mouse knockouts and pharmacological manipulations in zebrafish. These reveal that Sprouty genes direct the positioning of early midbrain neurons and are Wnt responsive in the midbrain. We propose a model in which Wnt regulates FGF activity at the isthmus by driving both FGF and Sprouty gene expression. This controls a dynamic, posteriorly retracting expression of her5 that directs neuronal differentiation in a precise spatiotemporal manner in the midbrain.